2009
DOI: 10.1080/02841850902902532
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic pulmonary angiography in the assessment of severity of acute pulmonary embolism and right ventricular dysfunction

Abstract: This study found that the parameters useful for distinguishing HUPE and HSPE included CTPA obstruction score, RV and SVC diameters, RV/LV short-axis ratio, interventricular septum shape, and reflux into the IVC. RV dilatation may be a significant predictor for mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 35 publications
0
28
1
2
Order By: Relevance
“…10 Our results show a highly significant association between the Qanadli score and RV/LV ratio, which is supported by other reports of a strong positive correlation between the mean obstruction score (calculated with the Qanadli method) and mean RV/LV ratio, a significant correlation between the Qanadli obstruction score and RV/LV ratio, and a correlation between RV/LV ratio and mortality. [22][23][24][25] Our results do not confirm those of Araoz et al who reported no correlation between RV/LV ratio and mortality rate. 24 In 108 consecutive patients, Ozsu et al showed the correlation of biomarkers and right/left ventricular dimension ratio ≥1.1 on CTPA with mortality.…”
Section: Figure4contrasting
confidence: 57%
“…10 Our results show a highly significant association between the Qanadli score and RV/LV ratio, which is supported by other reports of a strong positive correlation between the mean obstruction score (calculated with the Qanadli method) and mean RV/LV ratio, a significant correlation between the Qanadli obstruction score and RV/LV ratio, and a correlation between RV/LV ratio and mortality. [22][23][24][25] Our results do not confirm those of Araoz et al who reported no correlation between RV/LV ratio and mortality rate. 24 In 108 consecutive patients, Ozsu et al showed the correlation of biomarkers and right/left ventricular dimension ratio ≥1.1 on CTPA with mortality.…”
Section: Figure4contrasting
confidence: 57%
“…15 studies were initially excluded [10,19,20,22,26,31,33,35,38,39,41,43,46,50,52]. For six of them, the inclusion in the analysis was possible following contact with the authors [22,35,38,39,43,52].…”
Section: Meta-analysis Of Ct Assessed Right Ventricle Dilationmentioning
confidence: 99%
“…Another strength of our subjective interpretation strategy is that it mitigates ambiguity introduced from different RV/LV diameter ratio cutoff values used to predict outcomes, varying in the literature from 0.9 to 1.0 for 4-chamber measurements [8,9,13,17] and from 0.9 to 1.5 for axial measurements [6,12,14,15,17,18,[23][24][25]. We applied a 1.0 threshold for objective measurements when compared to visual assessment because it is supported by the data (Fig.…”
Section: Discussionmentioning
confidence: 98%